Indigeneity, Immigrant Newcomers and Interculturalism in Winnipeg, Canada. (July 2014) - Gyepi-Garbrah, John; Walker, Ryan; Garcea, Joseph
This paper examines how modern urban Indigeneity is influencing the integration of immigrant newcomers in Western settler cities. Using a case study of Ka Ni Kanichihk Inc. (KNK), an Indigenous organisation in the city of Winnipeg, Canada, this research contributes to the emerging framework of intercultural urbanism. Indigenous peoples and newcomers are living side-by-side in many neighbourhoods, with common histories of colonialism, racism and socioeconomic challenges. Interviews with staff and focus groups with Indigenous and newcomer participants of KNK programmes indicated that they are beginning their co-existence, mostly in inner-city neighbourhoods, with low levels of interaction, mutual misunderstanding, misperceptions, segregation and tension among youth in high schools. Through the initiatives of KNK and partner organisations, cross-cultural understanding and relationships are being built, overcoming social distance. There is great potential for building intercultural relationships among Indigenous peoples and immigrant newcomers as a means of decolonising Western cities.